A City Against Empire Transnational Anti-Imperialism in Mexico City, 1920-1930 - Lindner, Thomas K. (Liverpool University Press, 2023)
A City Against Empire is the history of the anti-imperialist movement in 1920s Mexico City. It combines intellectual, social, and urban history to shed light on the city's role as an important global hub for anti-imperialism, exile activism, political art, and solidarity campaigns. After the Russian and the Mexican Revolution, Mexico City became a space and a symbol of global anti-imperialism. Radical politicians, artists, intellectuals, scientists, migrants, and revolutionary tourists took advantage of the urban environment to develop their visions of an anti-imperialism for the twentieth-century. These actors imagined national self-determination, international solidarity, and an emancipation from what they called "the West." Global, local, and urban factors interacted to transform Mexico City into the most important hub for radicalism in the Americas. By weaving together the intellectual history of Mexico, the urban and social histories of Mexico City, and the global history of anti-imperialist movements in the 1920s, this books analyses the perfect storm of anti-imperialism in Mexico City.